LITHUANIAN SCOUTS PRESS PUBLISHING FROM 1990 TO 2013 - Venclovaitė, Vaiva (Knygotyra, 2016)
The article represents the results of research based on Lithuanian Scouts’ press from 1990 to 2013. Historical, social, cultural and ideological contexts of Scouting are taken into consideration. The main tasks of the research were to investigate the stimulus and value of scouts’ publishing; summarize the publishing intensity; analyze the printing culture of books and its influence to assortment; determine the geographical regularities of publishing; reveal the main publishers; sift the most significant periodicals; The analysis of the primary sources, historiography and bibliographical tools with an overall, scientific and specific book science methods, has led to the conclusion that the press of Scouts is one of the main tools to develop the structure as well as communicate, spread the information and transfer experience in the organization. In the broad sense, considering the value of Scouts’ press, it helps to maintain the continuity of the organization in question. While analyzing a thematic aspect of the subject matter, it has been determined that the press of Scouts’ organization is targeted at not just satisfying the inner demand of organization but getting some attention from the general public as well. This is done by publishing books on more abstract topics. The investigation of Scouts’ press geography and main publishers revealed that the main publishing centers in Lithuania were determined by economic and cultural status of the cities. In exile, it was predestined by historical circumstances. The press was most developed in Kaunas and Vilnius, as well as Germany and the United States of America. Depending on the historical factors, the network of publishers was changing. However, during all the historical periods there was always the main leader: during the interwar period of Lithuania, it was the Scout Association of Lithuania, in exile the leadership was taken over by the Lithuanian Scouts’ Association, after Lithuania regained independence (from 1990) it was ensured by the Lithuanian Scouting. The research of Scouts’ press has led to the conclusion that the printing culture of publications was mostly influenced by the conditions and geographical location of the historical period. A wider circulation and assortment of press could be noticed during the period of exile when the subdivisions of Scouts started to use the services of printing houses more actively, instead of using operational reproduction tools.